The physicochemical, antioxidant, and sensory properties of chocolate biscuits incorporated with encapsulated mangosteen (Garcinia mangostana L.) peel extract - Rossi Indiarto; Reni Reni; Gemilang Lara Utama; Edy Subroto; Aldila Din Pangawikan; Mohamad Djali (International Journal of Food Properties)
Chocolate biscuits are one type of biscuit that contains antioxidants, albeit in small amounts. Incorporating functional compounds into the product is an option for enhancing its quality. This study investigated chocolate biscuits’ physicochemical, antioxidant, and sensory properties incorporated with encapsulated mangosteen peel extract in percentages of 1%, 3%, 5%, and 7%. The increase in mangosteen peel extract microcapsules significantly affected the total value of polyphenols, flavonoids, peroxide number, color, and texture profile. But, there were no significant differences in the organoleptic characteristics of color, aroma, taste, texture, and overall acceptance. Total polyphenols, flavonoids, texture profile, a* and b* values, and browning index were all positively correlated with increasing the concentration of encapsulated in the formula. However, there was a negative correlation between antioxidant activity, peroxide number, and L*. It obtained the best recipe for its physicochemical, organoleptic, and antioxidant properties at 5%. Overall, the panelists approved the chocolate biscuits with mangosteen peel extract microcapsules. This product’s development is an alternative to antioxidant-rich functional foods.